Impact of once‐daily ER‐Tac on trough concentration variability in a stable AYA renal transplant recipient cohort. (18th May 2021) - Chandran, Mary Moss; Blanchette, Eliza; Goebel, Jens; Bock, Margret
Abstract: Background: Successful renal transplantation requires complex medication regimens that rely on strict adherence to be effective. Variability in immunosuppression exposure, specifically tacrolimus, is associated with poor allograft outcomes. Wide intra‐patient variability of tacrolimus trough concentrations (Vtac) is likely, in part, attributable to regimen complexity and poor medication adherence. Once‐daily tacrolimus formulations create opportunity to simplify therapeutic regimens, and this study aims to evaluate their impact on Vtac and ultimately transplant outcomes. Methods: This retrospective cohort study investigated stable (AYA) renal transplant recipients converted from (IR‐Tac) to (ER‐Tac). Subjects served as their own controls. Vtac was assessed by measuring the (SD) of serial tacrolimus trough concentrations prior to and at four time points post‐conversion to ER‐Tac over 24‐month follow‐up. Secondary outcome measures included graft function, infection rates, and effect on modifiable treatment‐related factors. Results: Twenty‐eight AYA subjects were converted from IR‐Tac to ER‐Tac. Vtac significantly improved following conversion and was sustained for 24 months (Vtac0 2.32 vs. Vtac24 1.11, p .017). Renal function remained stable, and (BPAR) rates were modest (14%). Mean pill burden was reduced by 15%, and 42.9% of subjects achieved a once‐daily medication regimen. Conclusions: Conversion from IR‐Tac to ER‐Tac in this AYA population significantly improved Vtac with sustained effect over 2 years. This effect is likely attributable in part to simplification of the medication regimen and presumably improved medication adherence. Such conversion does not appear to compromise graft function for at least 2 years post‐conversion.